Hodgsonia macrocarpa Cogn. (Cucurbitaceae): New Record for Flora of Nepal - Maden, Kamal; Rai, Ram Kumar (Our Nature, 2009)
Cucurbitaceae (Cucurbit family) includes about 268 genera in the world. Hara and Williams (1979) reported its altogether 21 genera, 30 species and 2 forma from Nepal, while Press et al. (2000) added 2 more varieties and 1 forma. The present paper communicates one more new genus for flora of Nepal, recorded in Churia and mid hills of eastern Nepal. The specimens were collected from Sindrang Village Development Committee (VDC) of Bhojpur district, at elevation of 700 m and Raja Rani Pond vicinity of Bhogateni VDC, Morang district, Koshi Zone (Churia Hills), at the elevation of 450 m. The specimens were identified with the help of literature (Grierson and Long, 1991). This additional species is Hodgsonia macrocarpa Cogn. Keywords: Hodgsonia macrocarpa, New record, Nepal doi: 10.3126/on.v6i1.1658 Our Nature (2008)6:78-79